Participating in the sharing economy: The role of individual characteristics - Anne Bäro; Felix Toepler; Timo Meynhardt; Vivek K. Velamuri (Managerial and Decision Economics, 2022)
The sharing economy is attracting increasing research attention. However, scholarly knowledge lacks understanding about the individuals who are the key players in this emerging phenomenon. This study uses an explorative approach to investigate the individual-level characteristics of sharing economy users and providers. We analyze a sample of 1170 respondents and reveal that socio-demographics (gender, age, and education), personality traits (Extraversion, Neuroticism, and Conscientiousness), and attitudes (interdependent self, materialism, sharing economy support, and perceived public value contributions) are significantly associated with people's activities in the sharing economy. Our results shed new lights into the academic debate about individual drivers of the sharing economy.
Keywords: 650